Identity Making as a Colonization Process, and the Power of Disability Justice to Cultivate Intersectional Disobedience - Phillip Andrew Boda (MDPI AG, 2022)
Intersectionality has been used to describe the products of difference but scholars who work intersectionally in the tradition of Disability Justice have argued that attention should focus on the process of identity making-those processes by which some Lives-Hopes-Dreams are positioned as more valuable and Whole because of our societies' commitments to racial capitalist coloniality. This work uses intersectionality as critical social theory, combined with broader cultural analyses of colonization as a process that did not stop within the creation of the Modern Western world, to visibilize identities often explicitly erased: students labeled with disabilities. Through excavating group-made artifacts from a larger research study, I show how intersectionally-disobedient grammars can serve to illuminate complex identity making beyond juxtaposed colonialities of power, and, therein, I situate this bricolage approach as an embodiment toward Disability Justice.